The Inhibitory Activity Test of Green Amaranth (Amaranthus hybridus L.) Leaf Ethanol Extract Using Ultrasound-Assisted Extraction (UAE) Method Against the Growth of Staphylococcus epidermidis - Anhar Muflih; Nita Triadisti; Annisa Salsabela; Islan Nor (Jurnal Farmasi Udayana, 2025)
Staphylococcus epidermidis is a microorganism often found on almost all skin surfaces. Uncontrolled growth of S. epidermidis can cause skin dysbiosis such as acne. Generally, doxycycline, clindamycin, and tetracycline are used as synthetic antibiotic agents for S. epidermidis, but the search for new natural antibiotic agents to treat acne due to S. epidermidis needs to be developed, such as green spinach leaf extract (Amaranthus hybridus L.). Green Spinach is known to have antioxidant, antianemia, anti-inflammatory, antihyperlipidemic, antidiuretic, antifungal and antimicrobial activities, duet to the presence of secondary metabolites, such as alkaloids, steroids, tannins, saponins, and flavonoids. This study aims to analyse the antibacterial activity of green spinach leaf ethanol extract by considering the extract's inhibition zone. Green spinach leaves were extracted by Ultra Assisted Extraction (UAE) with 96% ethanol, and testing was carried out using the disc diffusion method. The results of this study showed that spinach leaf extract with concentrations of 15%, 30%, and 45% gave sequential results of 11.3 ± 0.06 mm, 12.2 ± 0.1 mm, and 12.5 ± 0.1 mm, including the category of strong inhibitory response.